2015
DOI: 10.1590/s2179-975x0315
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nutrients increase on the copepod community of a reservoir using cages

Abstract: Aim: This study investigated changes in copepod abundance and the influence of environmental variables in a reservoir with fish farming using cages, on temporal and spatial scales. We hypothesised that the copepod abundance will increase when influenced by changes in environmental variables due the increase of nutrients originating from fish farming. Methods A 120-day sampling of copepods and environmental variables was carried out in a subtropical reservoir of the Paraná River basin (Rosana reservoir), upstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
0
5
0
1
Order By: Relevance
“…The water flow brings allochthonuous material (anthropic activities) resulting in an eutrophication process. According Tibúrcio et al (2015) abundance of the community of Copepoda increases due to alterations in environmental variables caused by the increase in the practice of fish farming. Themocyclops decipiens and A. furcatus adults were frequently abundant and shared habits in oligo-mesotrophic environments (Sipaúba-Tavares et al, 2011;Tibúrcio et al, 2015).…”
Section: Immentioning
confidence: 99%
“…The water flow brings allochthonuous material (anthropic activities) resulting in an eutrophication process. According Tibúrcio et al (2015) abundance of the community of Copepoda increases due to alterations in environmental variables caused by the increase in the practice of fish farming. Themocyclops decipiens and A. furcatus adults were frequently abundant and shared habits in oligo-mesotrophic environments (Sipaúba-Tavares et al, 2011;Tibúrcio et al, 2015).…”
Section: Immentioning
confidence: 99%
“…The abundance of the mesotrophic-eutrophic environments copepod bio-indicator Thermocyclops decipiens (Tibúrcio et al 2015) and the large amounts of Rotifera observed in both studied periods respond to the high nutrient and organic loadings always entering the pond. The differences in zooplankton species composition observed in both invasion periods seem not to be largely related to season, since 38 out of the 40 taxa in table 2 have been recorded during the rainy summer and during the dry winter either in this or in previous macrophyte studies conducted in this farm (Travaini-Lima et al 2016, Sipaúba-Tavares et al 2017.…”
Section: Discussionmentioning
confidence: 88%
“…Net cage fi sh farming in reservoirs is considered as a promising alternative to meet the increasing need for food of the world population (Alves & Baccarin 2005, Dias et al 2011, Tiburcio et al 2015. The increase of this activity is related to the exploitation of available reservoirs and lakes, high effi ciency in management, readiness of fi sh removal and continuous water fl ow that would theoretically improve the water quality inside the cages and reduce the production costs (Cyrino & Kubtiza 1996, Furlaneto et al 2006, Halwart et al 2007.…”
Section: Introductionmentioning
confidence: 99%